Structural behaviour of di-blended fibre reinforced concrete slab panel - Palanisamy, T.; Prabu, B. (Journal of Structural Engineering, 2024)
Plain Portland cement concrete is a brittle material. The strength of concrete in tension is much lower than in compression. A growing tensile crack in plain concrete can very soon lead to failure. In the presence of reinforcement, the tensile load is transferred to the steel. An alternative to increasing the load carrying capacity of concrete in tension is the addition of fibres. Well-dispersed fibres in the concrete act to bridge the cracks that develops in concrete. The incorporation of fibres in a cement matrix leads to an increase in the toughness and tensile strength, and an improvement in the cracking and deformation characteristics. In this investigation coir and steel fibres are used for slab panels. The optimum percentage of natural coir fibre in concrete was found as 0.25% with respect to cube compressive strength at the age of 28 days. Totally six slab panels (1500mm x 500mm x 90mm) are cast to find the behaviour under two point loading system. From this investigation the behaviour of steel fibre reinforced concrete slab panels yields better results when compared to the blended natural coir fibre reinforced concrete.